Simulasi dan Analisis Perubahan Sudut Dan Kecepatan Sudut Rotor Terhadap Perubahan Konstanta Koefisien Redaman Torsi Pada Model Single Machine Infinite Bus - Dibyo Laksono, Heru; Putra, Ravi Shidqi (Jurnal Ilmiah Giga, 2024)
The occupancy rate of the building has decreased due to the COVID-19 pandemic. Office buildings, hotels, apartments, and shopping centers experienced a decline in visitors. Meanwhile, some shops have stopped their business. The building management will continue to operate electrical equipment to support activities. The impact is that the load is unbalanced. This affects the load balance in the building. This condition will be detrimental and in the long term, will damage the transformer. The purpose of this study is to measure the level of electrical load balance in the Tang City Mall building. The measurement results on the existing 5-unit transformer show an unbalanced load between 0.63% to 4.76%. This measurement was carried out during rush hour conditions, namely at 17.30 WIB. Based on the calculation data, for a month, during a month you will experience a neutral current power loss of 2848kWh and a ground current power loss of 175 kWh. Instant measurements during mall opening and closing hours recorded a significant imbalance reaching 7.9% at trafo2. To avoid this, it is necessary to regroup, especially for single-phase loads. Meanwhile, building tenants' opening and closing hours must be simultaneous.